Study habits and self-regulated learning in university students - Terry Advíncula, Sandra Gabriela (2021)
The general objective of this research was to determine if there is a relationship between the variables study habits and self-regulated learning. The study design was a non-experimental cross-sectional correlational scope. The sample consisted of 90 students, out of a total of 280 students from the VIII cycle of the international business and administration career at a private university in Lima. The instruments used were questionnaires A and B. Once the results had been analyzed, it was evident that, for the sample of this study, between the variables study habits and self-regulated learning there is a significant positive statistical correlation of p <.05 and rho of Sperman of ρ = 0.890 **.